2021
DOI: 10.5114/aoms/124154
|View full text |Cite
|
Sign up to set email alerts
|

Parent-reported sleep problems in children and adolescents with sickle cell disease: relationship to health-related quality of life

Abstract: IntroductionChildren with sickle cell disease (SCD) can present a variety of clinical symptoms that may affect their sleep and health-related quality of life (HRQOL). This study aims to investigate the relation between sleep problems and HRQOL in children and adolescents with SCD.Material and methodsThe sample included 86 children and adolescents in the SCD patient group and 82 healthy controls, with an age range of 8-16 years. Subjects for the study were recruited from the Sickle Cell and Thalassemia Center o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Several studies reported high prevalence of OSA or sleep disturbance in children with thalassemia major. [8][9]30 Although PSG was the gold standard method for diagnosing resulting in stronger clinical significance, there are still limitations due to incorporating young children and sparse availability of long waiting lists and high costs. Simple screening tools are needed for children.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported high prevalence of OSA or sleep disturbance in children with thalassemia major. [8][9]30 Although PSG was the gold standard method for diagnosing resulting in stronger clinical significance, there are still limitations due to incorporating young children and sparse availability of long waiting lists and high costs. Simple screening tools are needed for children.…”
Section: Discussionmentioning
confidence: 99%
“…Parents' awareness of sleep disorders, social and cultural factors, and associated physical and mental disorders are plausible explanations. Despite the association of sleep problems with various preventable physical and mental disorders [21,22]. However, few researchers addressed this important issue in Saudi Arabia [10,11].…”
Section: Discussionmentioning
confidence: 99%